College Students' Perceptions Toward Usability of Simulator Application as a Form of Virtual Experiment at the Distance Learning - Nurdiana, Dian; Hasanah, Siti Hadijah; Maulana, Muhamad Riyan (International Journal of Global Operations Research, 2024)
The use of simulator applications as one of the learning media is used in face-to-face classes. Its use is rarely used to support distance learning. In fact, the distance learning process must have the same quality as face-to-face learning. The role of technology and media is one of the keys to success in conveying material to students. This study examines the use of simulator applications in distance learning in terms of its reusability. The simulator application used is Cisco Package Tracer on learning computer networks with modules as the main teaching material used by students. The use of this media aims to understand and practice computer network simulations. By involving 60 participants, a case study regarding usability feasibility was measured by using the USE Questionnaire which consisted of 4 usability dimensions: Usefulness, Ease of Use, Ease of Learning, and Satisfaction. The findings show that the use of simulator applications in distance learning gets good or positive responses in the context of usability. This shows that the use of simulator applications is suitable for use in distance learning.